Knowledge hiding in organization: A comprehensive literature review and future research agenda. (29th October 2021) - Garg, Neha; Kumar, Chitresh; Ganguly, Anirban
Abstract: Research on knowledge hiding has rapidly increased over the past decade, but findings have thus far not been systematically synthesized. This, therefore, has not only hampered the clarity surrounding the construct but also restricted growth in this line of research. The current study thus attempts to integrate the scattered KH literature through a systematic literature review to understand the growth of the KH construct, thereby synthesizing the extant research findings, as well as uncovering areas that require future research. Accordingly, 92 research papers were systematically searched, critically evaluated, and synthesized to make the available knowledge and evidence more accessible to scholars and practitioners. The synthesis not only answers some fundamental, yet blurred questions around the construct, but also provides a composite sense of diverse findings recorded in the extant literature that would assist in drawing conclusions and future decision‐making around knowledge hiding behaviors. It also maps out the relatively neglected areas that require more attention going forward and consequently proposes that the next decade should look forward to more compare and contrast studies from a socio‐economic, cultural, product‐specific, and industrial sector perspective. The study is expected to motivate academicians and researchers to advance the field theoretically by providing a constructive platform for future studies, in the process, advance the literature in this field. Further, it builds a worthwhile case for organizations to recognize the existence of knowledge hiding and judge the associated risks, benefits, and harms to make informed decisions.